Footnotes to Kraepelin: changes in the classification of mood disorders with DSM-5 - Kalk, Nicola J. (BJPsych Open, 2017)
SUMMARY: Reliable diagnosis of mood disorders continues to pose a challenge. This is surprising because they have been recognised clinically since classical times. Mood disorders are also common: major depressive disorder affects nearly 300 million people worldwide and bipolar affective disorder nearly 60 million and they are a major cause of disability. Nonetheless, the reliability trials of the updated Diagnostic and Statistical Manual, Fifth Edition (DSM-5) found that the reliability of the diagnosis of major depressive disorder was in the ‘questionable’ range. Although the reliability of the diagnosis of bipolar I disorder in the same trials was ‘good’, the sample size of the individuals recruited to validate bipolar II disorder was insufficient to confirm reliability. As the epidemiological prevalences of bipolar I and bipolar II disorders are the same, this alone implies problems in its recognition. Here, we critically evaluate the most recent iteration of DSM mood disorder diagnoses in a historical light and set out the implications for clinical practice and research. DECLARATION OF INTEREST: N.J.K. has attended educational activities funded by GlaxoSmithKline (GSK) and by Lundbeck and has worked on data from a study funded by Wyeth; her PhD was jointly funded by the Wellcome Trust and GSK. A.H.Y. has given paid lectures and is on advisory boards for the following companies with drugs used in affective and related disorders: Astrazenaca, Eli Lilly, Janssen, Lundeck, Sunovion, Servier, Livanova. He is Lead Investigator for the Embolden Study (Astrazenaca), BCI Neuroplasticity study and Aripiprazole Mania Study, which are investigator-initiated studies from Astrazenaca, Eli Lilly, Lundbeck, and Wyeth. COPYRIGHT AND USAGE: © The Royal College of Psychiatrists 2017. This is an open access article distributed under the terms of the Creative Commons Non-Commercial, No Derivatives (CC BY-NC-ND) license.